Enhancing Outcomes: Acceptability of Medication Formulations for the Treatment of Acute Agitation in a Psychiatric Population - Rachel E. Walker; Leigh Anne Nelson; Carrie Kriz; Courtney A. Iuppa; Yifei Liu; Lauren A. Diefenderfer; Ellie S. R. Elliott; Roger W. Sommi (MDPI AG, 2022)
BACKGROUND: There is limited research evaluating patient acceptability of medication formulations in the treatment of acute agitation. This study assessed patient acceptability of medication formulations (tablet, orally-dissolving-tablet [ODT], liquid, intramuscular injection [IM], inhaled device [INH]) for the treatment of acute agitation and examined correlating factors. METHODS: Adults with psychotic illness or bipolar disorder receiving emergency or inpatient services at an inpatient psychiatric facility in Kansas City, Missouri were included. Participants viewed a presentation on medication formulations for acute agitation and were surveyed on acceptability (measured on a five-point Likert scale). The primary outcome variable was the attitudinal measurement of acceptability of each formulation in correlation with the severity of agitation for use in themselves and other patients. RESULTS: One hundred participants completed the survey. Participants rated the following: (1) This medication formulation would be acceptable to treat mild agitation in themselves and others (oral tablet 85% and 48%; ODT 82% and 55%; liquid 74% and 51%; IM 53% and 74%; INH 78% and 72%); and (2) This medication formulation would be acceptable to treat severe agitation in themselves and others (oral tablet 75% and 52%; ODT 74% and 53%; liquid 66% and 53%; IM 61% and 67%; INH 77% and 72%). For treating mild agitation, participants preferred tablets and ODTs to the IM (p < 0.05) and the INH to liquid or IM (p < 0.05), for themselves; and oral formulations were preferred to the IM (p < 0.05) for other patients. For severe agitation in themselves and others, preference for the INH and IM versus oral formulations (p < 0.05) was significant, with no difference between the INH and IM (p > 0.05). CONCLUSIONS: The proportion of responses preferring oral formulations was higher than IM and INH. Dosage formulation acceptability differed depending on the severity of agitation and intended recipient of the medication.